The Students’ Perception of Using Webtoon Application at The Sixth Semester of The English Department - Rahmadani, Masitoh; Siregar, Fitri Rayani; Rambe, Sokhira Linda Vinde (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research investigates students' perceptions of using the Webtoon application in the sixth semester of the English Department at State Islamic University Syekh Ali Hasan Ahmad Addary Padangsidimpuan. A descriptive quantitative approach was used, with 30 students participating. The results showed that students perceived Webtoon positively for improving reading literacy, with 46.82% agreeing and 15.32% strongly agreeing. Students responded favorably to indicators of absorption, understanding, and evaluation. Webtoon was recognized as an engaging medium that helped solve reading difficulties.